Utilization of proteins and nucleic acids in the study of gene function: a comparative review - Mwololo, J.K.; Karaya, H.G.; Munyua, J.K.; Muturi, Phyllis W.; Munyiri, S.W. (My University, 2010)
Proteomics is one of the fastest growing areas in areas of research, largely because the global-scale analysis of proteins is expected to yield more direct understanding of function and regulation than analysis of genes. Protein structure characterizes its function and a protein sequence that relates to a known structure forms a basis for identifying gene function. Proteins are encoded by the genome (genes), and the set of proteins encoded by the genome, including the added variation of post-translational modification, constitute the proteome. The proteins are involved in nearly all metabolic activities, hence are part of the tools that make living machines work. The proteome is neither as uniform nor as static as the genome. However challenges encountered in identifying the biochemical and cellular functions of the many gene products which are currently not yet characterized has necessitated the use of the proteome. Gel electrophoresis techniques allow the separation of cellular proteins on a polymer according to their molecular weight and isoelectric point. The development of automated methods for the annotation of predicted gene products (proteins) with functional categories is becoming increasingly important. Compared to the study of the genetic code, proteomics may allow greater understanding of the complexity of life and the process of evolution due to the large number of proteins that can be produced by an individual organism. The measurable changes in protein profiles are also being used in diagnosis of emerging diseases. A major challenge to proteomics is that proteins are dynamic and interacting molecules, and their variability can complicate detailed studies on gene function. Nevertheless, measuring the intermediate step between genes and proteins i.e. the messenger RNA (mRNA) or the transcriptome bridges the gap between the genetic code and the functional molecules that regulate cell functions. This review examines protein amenability to prediction of gene function and the potential of proteomics in biological research.
Keywords: Protein; proteome; genome; annotation; transcriptome; genetic code